Portrayal of Human Rights Issues Existing in Pakistan: An Analysis of Newsweek (2005-2010) - Ayisha Khurshid (Social Science Review Archives, 2025)
The portrayal of human rights issues in media has been highly debated as most of the time they are not presented in the frame of human rights violations rather are tied with other political news. The present study analyses the portrayal of human rights issues existing in Pakistan through Newsweek. Due to limitation of time, articles from 2005 to 2010 are first collected and one article from each year is then analysed. 2005 did not have any article on human rights. The articles are analysed in the light of ideological square and perspectivising strategies. Among Perspectivising strategies, involvement strategies are scrutinized. The present paper concludes that human rights violations are tied with politics and in victims vs. victimized frame negative victimized and positive victims’ image is created. High degree of involvement strategies has also been observed and analyzed.